Prioritizing Sustainable Technological Solutions for Zero-Energy Buildings in Semi-Temperate Mountainous Climates Based on Technology Transfer Criteria - Atashbar, Fatemeh; Gholipour Gashninai, Mostafa; Ahmadi , Ferial (International Journal of Sustainable Energy Planning and Management, 2026)
In cold-mountainous climates, buildings face significant heating demands and complex environmental challenges that hinder the achievement of net-zero energy performance. This study presents a dual-focused framework integrating Multi-Criteria Decision-Making (MCDM) methods—Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS)—with technology-transfer criteria to evaluate and prioritize thirty sustainable technological solutions across three categories: building envelope, mechanical systems, and energy management. The framework emphasizes cost-effectiveness, technical maturity, and local compatibility to ensure practical applicability. Case-study comparisons from Turkey, Canada, and Switzerland demonstrate the transferability of optimized technological solutions. Results reveal that advanced high-performance insulation, dynamic glazing, and hybrid photovoltaic-thermal systems rank highest in combined energy savings and transfer potential. The proposed decision-support model offers policymakers and practitioners a robust tool for adapting global best practices to diverse cold-mountainous regions, contributing to the accelerated adoption of net-zero energy buildings worldwide.